1998
DOI: 10.1074/jbc.273.34.21675
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous SecA Catalyzes Preprotein Translocation at SecYEG

Abstract: SecA is found in the cytosol and bound to the plasma membrane of Escherichia coli. Binding occurs either with high affinity at SecYEG or with low affinity to lipid. Domains of 65 and 30 kDa of SecYEG-bound SecA insert into the membrane upon interaction with preprotein and ATP. Azide blocks preprotein translocation, in vivo and in vitro, through interacting with SecA and preventing SecA deinsertion. This provides a measure of the translocation relevance of each form of SecA membrane association. We now report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 41 publications
4
38
0
1
Order By: Relevance
“…Studies from a variety of groups over the past decade have revealed that SecA is a multidomain protein that can exist as a monomer or a dimer, and that its domain rearrangements can be triggered by binding to any of its several ligands. 67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The key to the conformational rearrangements appears to be intramolecular interactions that stabilize a more tightly packed, ''closed'' form of the protein. Weakening these interactions relieves these intramolecular constraints, and the protein domains partially dissociate, creating a less tightly packed, ''open'' form of the protein.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
“…Studies from a variety of groups over the past decade have revealed that SecA is a multidomain protein that can exist as a monomer or a dimer, and that its domain rearrangements can be triggered by binding to any of its several ligands. 67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The key to the conformational rearrangements appears to be intramolecular interactions that stabilize a more tightly packed, ''closed'' form of the protein. Weakening these interactions relieves these intramolecular constraints, and the protein domains partially dissociate, creating a less tightly packed, ''open'' form of the protein.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
“…Although the observed increase in specific activity of SecA labeling appears to be lower than the increase in SecYEG overproduction, we have shown previously that only a fraction of overproduced SecYEG protein properly assembles in the membrane where it gives rise to an increase in SecA high affinity binding sites and SecA-dependent translocation ATPase activity (42). However, we cannot rule out the possibility that some of the MPB-labeled residues of SecA arose from periplasmic exposure of a phospholipid-bound pool of SecA, although such speculation is inconsistent with the extractability of this pool of SecA by reagents that classically remove only peripherally bound membrane proteins (15). In addition, this latter concern is inconsistent with our data given below.…”
Section: Construction Of Monocysteine Seca Mutants and In Vivomentioning
confidence: 81%
“…Conclusive evidence on this latter point must clearly await better structural analysis of the SecA-SecYEG complex in its various translocation states. It is conceivable that some of our MPB-labeled residues were the result of periplasmic exposure of phospholipid-bound SecA protein, although this possibility seems unlikely because lipidic SecA has been described as peripheral in nature based on its dissociation from the membrane during sucrose gradient purification or by treatment with chaotropic reagents such as urea (15). Furthermore, SecYEG-bound SecA was found to be shielded from phopholipid acyl chains in a photo-cross-linking study (50), indicating that SecYEG-bound SecA does not appear to possess any sizable phospholipid-associated domain.…”
Section: Construction Of Monocysteine Seca Mutants and In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…We tested the secretion-proficient secA mutants for their sensitivity, supersensitivity, or resistance to sodium azide, an inhibitor of SecA membrane and translocation ATPase activities (21,53), since mutations within SecA's nucleotide-binding domains often affect this property (52,54). This test was done under conditions where only the mutant form of SecA protein was produced (the secA13(Am) supF(Ts) pT7secA-his-bearing strain at 42°C).…”
Section: Fig 3 Atp-dependent Helicase Activity Of Seca Proteinmentioning
confidence: 99%